LA EDUCACIÓN POPULAR Y LA PARTICIPACIÓN POLÍTICA CIUDADANA (2016)
This paper reviews and investigates the analysis that exists in the construction of citizenship through popular education, leading to enhance opportunities for citizen participation through mass recognition of institutions designed to control the activity of their representatives as well as the legal tools to visualize their participatory action, both through direct and face exercise as interactive media.